P.102 Expanded endoscopic endonasal approach for orbital apex decompression. (June 2019) - Yang, K; Ellenbogen, Y; Algird, A; Sommer, D; Reddy, K
Abstract : Background: The Endoscopic endonasal approach (EEA) has been gaining popularity in the past decade as an alternative to traditional transcranial and transorbital approaches. We have performed orbital apex decompression for a variety of pathological entities. Methods: We performed a retrospective chart review on patients who underwent EEA orbital apex decompression between January 1 st 2010 and December 1 st 2018 at McMaster University. Results: Eight patients underwent endoscopic endonasal orbital decompression at our center, including five male patients and three female patients. The mean age of our patients was 50.1 years. The different pathologies we treated included nasopharyngeal carcinoma, hemangioma, fibrous dysplasia, IgG4 disease, inverted papilloma, angioleiomyoma, and neuroendocrine paraganglioma. Five patients presented with visual symptoms. Postoperatively, one of these five patients improved to baseline, three had stable vision, another one had progressive visual decline despite surgical intervention. Conclusions: Endoscopic endonasal approach can be used as an alternative to decompress orbital apex pathologies in selected patients.